Fenomena Jual Beli Online dari Tinjauan Herbert Marcuse : Studi Kasus Mahasiswa Pendidikan Sosiologi Unismuh Makassar - Sri Wahyuni; Reski Aulia. r; Marlia Herman; Riska Riska (Politeknik Kampar, 2025)
This study examines the phenomenon of online buying and selling among students in the Sociology Education study program through a qualitative approach. The research aims to explore how Herbert Marcuse’s theory and the concept of alienation can be applied to understand students’ engagement with online shopping platforms. Data were collected through in-depth interviews and analyzed using content analysis to identify patterns of behavior, perception, and meaning related to online commercial activities. The findings reveal that online buying and selling are not merely economic practices but also social and psychological phenomena that shape students’ interactions, identities, and lifestyles. The study highlights how students experience both empowerment and alienation through digital consumerism—where convenience and self-expression coexist with dependency and loss of authenticity. Furthermore, the results indicate that online platforms have become spaces for social interaction and self-construction, yet they may also reinforce consumerist tendencies that distance individuals from genuine social relations. These insights contribute to a deeper understanding of how technological engagement intersects with classical sociological concepts, particularly alienation, within contemporary student life. The research also offers implications for sociology education, emphasizing the importance of critical awareness regarding technology’s role in shaping social experiences.